2019
DOI: 10.1021/acs.orglett.9b02804
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Discovery of Pentaketide Ansamycin Aminoansamycins A–G

Abstract: Ansamycins are a class of macrolactams with diverse bioactivities, characterized by the unique 3-amino-5-hydroxybenzoic acid moiety. In this study, the ansamycin gene cluster aas in Streptomyces sp. S35 was activated by the constitutive coexpression of two pathway-specific regulator genes aas1 and aas10, and seven novel pentaketide ansamycin aminoansamycins A–G (1–7) were identified. Compound 4 with better antiproliferative activity indicated that the anthranilate analogues are probably promising building bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The most active derivative, 30 decorating with an anthranilate motif, revealed quite potent antiproliferative activities (IC 50 s ¼ 7-10 mM). 124 The absence of the anthranilate or AHBA motifs at C(9) (29) decreased potency at least by 2-fold or even contributed to the loss of activity, similarly to the oxidation of the ansamycin core (32,33).…”
Section: Benzene-and Benzoquinone-c 9 Ansamycins Obtained By Genetic ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The most active derivative, 30 decorating with an anthranilate motif, revealed quite potent antiproliferative activities (IC 50 s ¼ 7-10 mM). 124 The absence of the anthranilate or AHBA motifs at C(9) (29) decreased potency at least by 2-fold or even contributed to the loss of activity, similarly to the oxidation of the ansamycin core (32,33).…”
Section: Benzene-and Benzoquinone-c 9 Ansamycins Obtained By Genetic ...mentioning
confidence: 99%
“…S35, isolated from soil (Kunming, Yunnan, China). 124 The AasD hydroxylase takes part in the biosyntheses of 29–33 , which is analogous to Nam7 , active in the neoansamycins biosynthesis. Ansamycins 30–33 contain nonproteinogenic AHBA and anthranilate motifs attached to the C(9) position of their ansa chains (Fig.…”
Section: Mutasynthetic and Genetic Manipulation Strategies Opening Ac...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the first maytansines found in plants [ 4 ] are now known to be produced by the interplay amongst bacteria in the root system [ 5 ]. It was reported that nearly 300 ansamycins have been identified from natural sources [ 6 ] and more and more ansamycins continue to be reported, such as the recently described olimycins from the ovmO -inactivated mutant strain Streptomyces olivaceus SCSIO T05 [ 7 ] and ansaseomycins from a heterologous mutant strain of Streptomyces seoulensis [ 8 ]. The ansamycins exhibit diverse biological activities, such as antibacterial (naphthomycin A, rifamycin, rubradirin and streptovaricin A), anticancer (ansamitocins P-3, ansatrienins A, geldanamycin, mitomycin C, saliniketals A and B), lipoxygenase inhibitory (tetrapetalones A and B) and antiviral (divergolide O) activities [ 1 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Lu and co-workers continuously isolated and elucidated an array of structurally novel pentaketide ansamycins named microansamycins A–I and aminoansamycins A–G through a gene activation approach (Figure ). Quite recently in 2022, Igarashi and co-workers reported the isolation of three novel ansamacrolactams from the culture extract of the genus Catellatospora , a rare actinomycete . However, the poor accessibility of these materials severely limited further and systematic biological screening.…”
mentioning
confidence: 99%